2015
DOI: 10.1186/s12888-015-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

Health facility determinants and trends of ICD-10 outpatient psychiatric consultations across Sofala, Mozambique: time-series analyses from 2012 to 2014

Abstract: BackgroundFew peer-reviewed publications have taken a longitudinal or systems approach to mental healthcare (MH) utilization in low- and middle-income countries. We analyzed: (1) outpatient ICD-10 diagnoses over time and by gender; and (2) health facility determinants of MH service utilization.MethodsWe reviewed a census of 15,856 outpatient psychiatric consultations conducted at Ministry clinics in Sofala province, Mozambique from January 2012-June 2014. Generalized estimating equations were used to model fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…In 1994, the Ministry of Health implemented a task-shifting strategy through the development of a 30-month psychiatric technician training program, in which mid-level professionals are trained to provide mental health services in primary care settings [23]. This strategy has increased availability of mental health services, and this new cadre of health professionals currently provide the vast majority of psychiatric services nationwide [23,24]. Despite this strategy, there is a significant shortage of mental health professionals and limited health system capacity to bring evidence-based mental health interventions to scale.…”
Section: Depression and Suicide In Mozambiquementioning
confidence: 99%
“…In 1994, the Ministry of Health implemented a task-shifting strategy through the development of a 30-month psychiatric technician training program, in which mid-level professionals are trained to provide mental health services in primary care settings [23]. This strategy has increased availability of mental health services, and this new cadre of health professionals currently provide the vast majority of psychiatric services nationwide [23,24]. Despite this strategy, there is a significant shortage of mental health professionals and limited health system capacity to bring evidence-based mental health interventions to scale.…”
Section: Depression and Suicide In Mozambiquementioning
confidence: 99%
“…This is an urgent need in Mozambique, as the existing specialized psychiatric care system focuses almost exclusively on severe mental illness, including schizophrenia and epilepsy. Initial pilot work has shown that less than 3% of all mental health consultations across Sofala Province and less than 2% of all consultations at the Beira Central Hospital were for any mood disorder [23,24]. This suggests that a large burden of depression is missed in existing psychiatric care settings [25].…”
Section: Introductionmentioning
confidence: 99%
“…This is an urgent need in Mozambique, as the existing specialized psychiatric care system focuses almost exclusively on severe mental illness, including schizophrenia and epilepsy. Initial pilot work has shown that less than 3% of all mental health consultations across Sofala Province and less than 2% of all consultations at the Beira Central Hospital were for any mood disorder (22,23). This suggests that a large burden of depression is missed in existing psychiatric care settings.…”
Section: Introductionmentioning
confidence: 99%